Retraction statement - Peruana de Biología, Editor Revista (2019)
We, the Editor and Editor Committee of Revista Peruana de Biología (RPB) have retracted the article: “Barros Gomes P.R., Batista Reis J., Pêssoa Fernandes R., Mouchrek Filho V.E., Gouveia de Souza A., Alves Fontenele M. and Caetano da Silva J. 2019. Toxicity and molluscicidal activity of the essential oil Pimenta dioica against the snail Biomphalaria glabrata. Revista Peruana De Biología 26 (1), 101-8. https://doi.org/10.15381/rpb.v26i1.15913.”